Porous TiO2 Thin Film for Egfet pH Sensing Application - A. Zulkefle, M.; A. Rahman, R.; Rusop, M.; F. H. Abdullah, W.; H. Herman, S. (International Journal of Engineering and Technology, 2018)
Porous TiO2 thin film with nanostructure networks were produced through post-deposition etching-immersion method. TiO2 thin film was first fabricated using sol-gel spin coating and immersed in 5 M NaOH solution to obtain the porous structure. The nanostructure network exhibit branches with the size ranging from 9.01 nm to 11.39 nm while the distance between the branches varied between 16.64 nm to 83.04 nm. From the atomic force microscopy image, the surface roughness of the porous film was 5.049 nm, as expected, higher than the un-etched TiO2 sample. The porous film was then applied as the sensing membrane for an extended-gate field effect transistor (EGFET) pH sensor. The pH sensitivity of the porous film was 19.30 mV/pH with linearity of 0.9550, indicating that the porous film also has the ability as the sensing membrane of an EGFET pH sensor.Â Â